2016
DOI: 10.1111/acps.12584
|View full text |Cite
|
Sign up to set email alerts
|

European Union investment and countries’ involvement in mental health research between 2007 and 2013

Abstract: EU funding of mental health research does not match the burden incurred by mental disorders and must be increased in the next framework programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A more recent report on participation found that in FP7 21% of all projects involved at least one EU-13 organizations, and in the Horizon 2020 programme this ratio had fallen to 17% [25]. A recent study also confirmed that EU research grant allocation did not match the country specific burden incurred by mental disorders, and Eastern-European member states were underrepresented among beneficiaries [26].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report on participation found that in FP7 21% of all projects involved at least one EU-13 organizations, and in the Horizon 2020 programme this ratio had fallen to 17% [25]. A recent study also confirmed that EU research grant allocation did not match the country specific burden incurred by mental disorders, and Eastern-European member states were underrepresented among beneficiaries [26].…”
Section: Discussionmentioning
confidence: 99%
“…Though any research aimed at finding, testing or understanding the nature and treatment of mental disorders is potentially valuable, limited resources set constraints and impose defining priorities. Mental health funding is usually limited (Hazo, et al, 2016), though with significant discrepancies across countries (Hazo, et al, 2017). Funding calls and reports make it clear certain topics are prioritized.…”
Section: Are Research Decisions Based On Questions Relevant To Users mentioning
confidence: 99%
“…We extracted the 25 783 research projects funded by the European Commission's Directorate for Innovation and Research between 2007 and 2013. Methods and results of this query have been published elsewhere (Hazo et al, 2016) and will not be displayed in detail in the present paper.…”
Section: Part 2 -Searching Of Databasesmentioning
confidence: 99%
“…Several publications provided the share of health research funding dedicated to MHR in comparison with the share of burden of diseases occupied by mental disorders, sometimes comparing these indicators with others. They repeatedly showed discrepancies: first between the share of health funding dedicated to MHR in comparison with the share of total DALYs attributable to mental disorders, sometimes in comparison with such indicators in other nosographic fields (Chevreul et al, 2012, Christensen et al, 2011, Hazo et al, 2016, Hazo et al, 2017, Gandré et al, 2015, Kingdon, 2006, Kingdon and Wykes, 2013; and second discrepancies between groups of mental disorders' share of DALYs and funding attributed respectively (Batterham et al, 2016, Christensen et al, 2013, Jorm et al, 2002, Murray et al, 2017. Although the published estimations of the impact of MHR are high (Hickie et al, 2005, Scott, 2005, Kelly et al, 2006, Guthrie et al, 2016, Henderson, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation